Application of Numbered Head Together (NHT) Learning Model in Human Digestive System Material in Class VIII Students of Frater Junior High School Makassar - Yusniar Rasjid; Herlina, Herlina (ARRUS Journal of Social Sciences and Humanities, 2025)
This research is an experimental study that aims to determine the differences in science learning outcomes after applying the Number Head Together (NHT) learning model to 8th grade students at Makassar Frater Junior High School. This research is experimental using a pre-post test design. The population in this study were all students in grade VIII of SMP Frater Makassar, while the sample used purposive sampling technique totaling 29 students who were taught with the Number Head Together learning model. The results of this study indicate that the average learning outcomes of students taught before the NHT learning model were 69.48 and the average learning outcomes after the application of the NHT learning model were 79.66. Based on the results of the paired T test, it shows that the tcount value = 3.38 and obtained the Sig value level of 0.002 <0.05%. Thus it can be concluded that H1 is accepted, meaning that the application of the Number Head Together (NHT) learning model can improve the learning outcomes of Class VIII Students of Frater Junior High School Makassar.